A qualitative investigation of the career paths of individuals working in an information technology environment - Wilson, Gina (My University, 2002)
The aim of this research was to investigate the career paths of individuals working in an Information Technology (IT) environment. The focus of the study is on the career history, subjective career views and career expectations and aspirations of these individuals. The study is exploratory and involved in-depth semi-structured interviews with nine individuals working in an IT environment in one financial institution. Results indicate that the career paths of these individuals no longer follow the traditional approaches to Career Development (CD), but rather amalgamate aspects of the traditional with the less traditional CD approaches. The results also indicate that the emphasis of CD is increasingly becoming the responsibility of the individual themselves, thereby requiring a more proactive and self-directed Career Management (CM) style. The results are discussed and interpreted in light of the literature reviewed.
Thesis (M.A.)--University of the Witwatersrand, Arts Faculty (Industrial Psychology), 2002
Keywords: Career development -- South Africa; Information technology -- South Africa; Vocational guidance -- South Africa; Organizational change -- South Africa